Sosialisasi Pembuatan E-Modul pada Pembelajaran Matematika - Lois Oinike Tambunan; Janwar Tambunan (Journal on Education, 2023)
Community service activities in the form of outreach are carried out at the Patmos Learning House which aims to enable teaching staff at the learning home to make and use E-Modules in the learning process being carried out. Making E-Modules for learning mathematics can increase the competence of educators in developing and implementing them in the learning process. The dissemination of community service in this form of socialization is that educators in providing effective and efficient learning can attract and stimulate students' creativity to improve the learning process in schools in the era of the industrial revolution 4.0. The results of this socialization found that the creation and use of E-Modules could improve the quality of students' abilities. The results of this activity are 1) teachers become more confident and motivated to use technology, 2) teachers can design and create simple interesting learning E-Modules according to the themes and needs of students 3) teachers can design interactive videos and involve children in learning.